Reproduksi dan Endokrin - Sabrina Fadilah Diana Danifah; Nabila Meilani Nur Azzahrra; Nur Indah Ramadhani; Steffy Desiandra Puteri; Liss Dyah Dewi Arini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Why is it important reproductive and endocr'ine system ,s rmportanl for someone io be learned by s1udying embryology? Both of lhese syslems, reproductive and endocrine systems ure the most interconnected in lhe study of embryology. f'or example, when spermaiogenesis (sperm for-ma1ion process), will be studied how the male sex glands as the production of sperm, and then at the end of the study as well as the hormonal regulation of spermatogenesis. In the second chapter of this book discussed on the reproduclive syslem, including ultra strucrure and fsiologis of male and female reproduc1ive systems. In lhe next section, is also discussed about the endoc-rine system.